Mechanical integrity of 18650 lithium-ion battery module: Packing density and packing mode - Liu, Binghe; Zhang, Jinjie; Zhang, Chao; Xu, Jun (Engineering failure analysis, 2018)
The crash safety of lithium-ion batteries (LIBs) has recently become a hot research topic because of the wide application of LIBs in vehicle. This paper investigates how packing design of battery cells influence the energy density (volume specific) and structural of LIB pack. Firstly, three packing geometrical parameters (one packing angle parameter and two cell number parameters) are extracted to describe the packing modes, packing density and sizes of the module. Then a detailed computational model is established and validated through experiments, with the implementation of a failure criterion for short-circuit. An anisotropic elasto-plastic model is introduced to describe the mechanical response of the cylindrical jellyroll. Based on the computational results, we quantitatively describe the relationship between structural strength and packing parameters of battery module. The deduced empirical equations from the model are validated against numerical examples, and provide a reliable path to predict the mechanical integrity of battery packs with the knowledge of packing information. This developed modeling approach can serve as an efficient tool for safety design of LIB packs. [Display omitted] •Finite element models are introduced to describe the mechanical behavior and short-circuit onset of 18650 LIB packs.•The results quantify the relationship of packing design and energy density of LIB packs.•A convenient method is given to express the mechanical properties of battery packs.